Political Cycles in a Developing Economy : Effect of Elections in Indian States - Khemani, Stuti (World Bank, Washington, DC, 2015)
The author studies the effect of state legislative assembly elections, on the policies of state governments in 14 major states of India, from 1960 to 1996. She identifies the effect of the timing of elections using an instrument for the electoral cycle that distinguishes between constitutionally scheduled elections, and midterm polls. She contrasts two levers of policy manipulation - fiscal policy and public service delivery - to distinguish between alternative models of political cycles. The predictions of three models are tested: 1) Populist cycles to woo uninformed and myopic voters. 2) Signaling models with asymmetric information. 3) A moral hazard model with high discounting by political agents. The empirical results for fiscal policy show that election years have a negative effect on some commodity taxes, a positive effect on investment spending, but no effect on deficits, primarily because consumption spending is reduced. With regard to public service delivery, elections have a positive and large effect on road construction by state public works departments. Strikingly, the fiscal effects are much smaller than the effect on roads. The author argues that the pattern of evidence is inconsistent with the predictions of models of voter myopia, and asymmetric information. She explores an alternative moral hazard model in which the cycle is generated by high political discounting, and career concerns persuade politicians to exert greater effort in election years on the management of public works.